An Innovative Kefir Produced from Lactose Hydrolyzed Goat Milk with the Addition of the Probiotic Saccharomyces Boulardii: Volatile Compound Profile, Rheological and Sensory Properties - Kocak, Ali; Sanli, Tuba; Altinay, Canan; Tekin, Ali; Gurcan, Ismayil Safa; Hayaloglu, Ali Adnan (Springer, 2026)
The rationale for this study was that using Saccharomyces boulardii as a probiotic, particularly in kefir and similar fer-mented milk products made from goat's milk, could provide an innovative approach to enhancing health benefits and overall sensory acceptability. This study investigates the incorporation of S. boulardii into lactose-hydrolyzed goat's milk for kefir production and evaluates its impact on functional, microbiological and sensory characteristics during 28-day storage period. Goat's milk to be used in the production of lactose-reduced and lactose-free alternatives was subjected to 50% and 100% lactose hydrolysis with beta-galactosidase, and kefir samples were produced with and without the addi-tion of S. boulardii. The results showed that, increased glucose and galactose content due to lactose hydrolysis improved fermentation efficiency. Lactobacillus spp. counts peaked at 8.57 log CFU/mL in LH100B, while S. boulardii maintained viable levels above 10(6) CFU/mL throughout storage, meeting probiotic criteria. Proteolytic activity and antioxidant capac-ity increased significantly, especially in lactose-hydrolyzed samples with S. boulardii. Antioxidant capacity (ABTS assay) reached its highest value on day 14, showing up to 28-30% higher radical scavenging activity in S. boulardii containing samples compared to control. The level of lactose hydrolysis, particularly in combination with S. boulardii, significantly influenced technological and biochemical properties. The highest water-holding capacity was observed in the 100% hydro-lyzed sample with S. boulardii, while lactose hydrolysis increased the consistency index without affecting flow behavior. Although hydrolysis alone did not markedly alter the volatile profile, samples containing S. boulardii were characterized by alcohol-dominant volatiles. Additionally, lactose hydrolysis reduced citric and malic acids, whereas acetic acid levels remained elevated in samples containing S. boulardii throughout storage. Sensory evaluation showed that kefir produced from 50% lactose-hydrolyzed goat's milk with S. boulardii received the highest overall acceptability score from the pan-elists, while samples with 100% lactose hydrolysis also maintained favorable sensory characteristics. The results suggest that the combination of lactose hydrolysis and incorporation of S. boulardii enhances the functional, rheological, and sensory properties of kefir made from goat's milk, offering a promising strategy for developing fermented dairy products suitable for lactose-intolerant consumers and the functional food market.
Keywords: Fermented milk; Small ruminant milk; Lactose hydrolysis; Organic acids in fermented dairy products; Saccharomyces boulardii